Additive manufacturing of high-voltage electronics for gamma ray sensors - Burgett, Devin James (Kansas State University, 2023)
Recent efforts in the field of additive manufacturing have included the construction of three-dimensional circuits. Circuits constructed through additive manufacturing have the potential to reduce the volume and weight of a design by using space more efficiently. However, research in additive circuitry is usually concerned with low-voltage electronics such as low power sensors and environmental monitoring. In this work, a hybrid process to construct high-voltage electronics was developed. A compact high-voltage power supply for a photomultiplier tube was constructed through a combination of additive and traditional manufacturing processes. Advantages of individual processes were leveraged to reduce the volume and weight of the circuits constructed. Process methodology and parameters for fused deposition modeling, milling, automated placement, topographic scanning, and direct writing of conductive paste are covered. The dielectric is constructed using fused deposition modeling, with discrete slots for components. Surface roughness left behind by fused deposition modeling was greatly reduced through surface milling. Discrete components were placed into the build and the build surface was scanned to set the height for trace deposition. Finally, conductive material was deposited on the build surface to form circuit connections. The compact electronics constructed were electrically tested and compared against a commercially manufactured high-voltage resistive divider base for electrical performance, volume, and weight. A high-voltage power supply was constructed which could produce up to -881 V ± 0.68 % with a stability of within less than 0.4 %. The high-voltage power supplies constructed were able to reduce the volume by up to 29.75 %, and the weight by up to 41.7 % compared to the resistive divider base. The electrical performance of the high-voltage bases were comparable to voltages from the commercial board and are expected to allow the photomultiplier tube to function similarly.
Keywords: Additive manufacturing; 3D printing; High-voltage power supply; Cockcroft-Walton voltage multiplier; Compact circuit; Circuit layout